People as property: Representations of slaves in early American newspaper advertisements - Susanna Mäkinen (De Gruyter, 2022)
Using van Leeuwen's (1996) categories of social actor representations, this paper investigates the ways in which slaves were represented in four types of slavery-related advertisements (for sale, want to buy, runaways and captured runaways). The materials consist of 860 notices in total, and they are collected from eighteenth and nineteenth -century newspapers in Massachusetts, New York, Virginia and South Carolina. Of particular interest are the two aspects simultaneously present in slavery: how the advertisements can represent their subjects, on the one hand, as human individuals and, on the other hand, as someone’s property. The study examines, for example, the use of nomination and various kinds of categorization strategies used to represent the slaves, as well as the ways in which they are explicitly referred to as “property”. Examination of the advertisements shows that the representational strategies differ somewhat depending on the type of advertisement as well as the geographical area. Furthermore, the various representational possibilities also indicate that the advertisers could, by their word choices, choose either to highlight the slaves’ status as property or to leave it more implicit in the texts.